Application of Hydrous Bismuth Oxide for Arsenic Removal from Aqueous Solutions - Ranjan M.; Singh P.K.; Srivastav A.L. (My University, 2025)
The present study is devoted to arsenic sorption on hydrous bismuth oxide (HBO) through batch and column studies. Advantage of the adsorbent includes arsenic removal in addition to the simultaneous removal of nitrate and fluoride from aqueous solution. Both the forms of arsenic tested by adsorbent in which affinity for arsenic (V) was found better than arsenic (III). Langmuir isotherm and pseudo-second-order kinetic models were found a fit with the experimental data. Calculation of adsorption energy and increased level of chloride in treated water indicated the possible role of physical adsorption and ion exchange phenomenon in arsenic(V) sorption. A fixed bed column study gave 615 mL of treated water [As (V) < 0.01mg/L] from 0.085 mg/L arsenic (V) spiked influent with a sorption potential of 13.1-19.6 μg/g. XRD and EDS analyses confirmed the adsorption of arsenic (V) and the presence of chloride in the exhausted bed of adsorbent. The thermodynamic parameter has shown the endothermic and spontaneous process of adsorption. © 2021 Technoscience Publications. All rights reserved.